2020
DOI: 10.1186/s12905-020-00944-4
|View full text |Cite
|
Sign up to set email alerts
|

Modern contraceptive use among postpartum women living with HIV attending mother baby care points in Kabarole District, Uganda

Abstract: Background: Preventing unintended pregnancies among women living with HIV is important for improving maternal and child health outcomes. Despite multiple contacts between postpartum women and healthcare providers at health facilities, modern contraceptive use during postpartum period remains low even among women with intentions to limit or delay childbearing. We estimated postpartum modern contraceptive use, unmet need and factors associated with modern contraceptive use among HIV positive women attending moth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Low contraceptive use, especially modern methods like condoms and hormonal contraceptives, contributes to the high prevalence of unintended pregnancy among YWLHIV. For example, in Uganda, only 39.8% of adolescent girls and young women use modern contraceptives, and male condom use is as low as 19.7% [ 13 ]. Similarly, in South Africa, only 12.4% of the adolescent mothers living with HIV were found to use male condoms [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Low contraceptive use, especially modern methods like condoms and hormonal contraceptives, contributes to the high prevalence of unintended pregnancy among YWLHIV. For example, in Uganda, only 39.8% of adolescent girls and young women use modern contraceptives, and male condom use is as low as 19.7% [ 13 ]. Similarly, in South Africa, only 12.4% of the adolescent mothers living with HIV were found to use male condoms [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The finding that receipt of FP information during delivery is not associated with contraceptives contradicts findings by Jalang'o and colleagues [18] in which uptake of postpartum FP was significantly associated with counseling of women on various types of contraceptives. Findings from a similar study in Uganda showed that there are still missed opportunities for FP service provision at the mother-baby care points despite integration of services at such outlets [30]. As such even when postpartum women have numerous encounters with healthcare providers, they are unable to receive timely FP services.…”
Section: Plos Global Public Healthmentioning
confidence: 99%